Pigtail catheter "propping" for MitraClip percutaneous transcatheter mitral valve repair. Issue 2 (9th March 2016) - Sandhu, Kully; Butler, Robert; Large, Adrian
Abstract : In recent years percutaneous therapy has emerged as a feasible and effective option for the treatment of mitral regurgitation, particularly in cases where the risks of conventional cardiac surgery are prohibitively high. To date the most widely used percutaneous approach is beating heart, edge‐to‐edge repair with the MitraClip device (Abbott Vascular‐Structural Heart, Menlo Park, CA). The technique requires simultaneous grasping and approximation of both mitral valve leaflets prior to securing and releasing the clip. However, this may be technically challenging or indeed impossible in patients with failure of coaptation, particularly when there is a large coaptation gap. We present an approach for overcoming this relatively common obstacle based on "propping" the anterior mitral valve leaflet toward its posterior counterpart with a diagnostic pigtail catheter to reduce the coaptation gap and to allow grasping of both leaflets without difficulty. © 2016 Wiley Periodicals, Inc.